A room simulation tool for thermal comfort control in a bioclimatic building: A real example of use with an optimal controller. (21st March 2014) - Castilla, M.; Bonilla, J.; Álvarez, J.D.; Rodríguez, F.
Summary: A key objective in the European Union climate and energy package for 2020 is the reduction of energy consumption. Buildings are responsible for more that one third of global energy consumption, where heating, ventilation, and air conditioning systems account for more than half of it. In extreme climates, the existing passive measures of bioclimatic buildings are not enough at time to maintain a suitable users' thermal comfort. However, this thermal comfort must be reached reducing the energy spent by the heating, ventilation, and air conditioning system of the building. Control systems, and more specifically model predictive control, are a suitable way to find a trade‐off between users' thermal comfort and energy saving. Simulation tools are essential for the efficient and automated testing and validation of these control strategies. This paper presents a simulation tool of an office room from a bioclimatic building, namely, the CDdI‐CIESOL‐ARFRISOL building, to test advanced control strategies against a simulation model, to evaluate them, in terms of users comfort and energy consumption, and to validate them, considering the real room itself. Details about the simulation tool are given, together with the evaluation of its goodness through a real test using a nonlinear model predictive control in an office room of that building. Copyright © 2014 John Wiley & Sons, Ltd.